Study of 6Li exclusive breakup on 28Si target at 13 MeV - Patronis, N.; et al., - (HNPS Advances in Nuclear Physics, 2020)
We have undertaken the study of the 6Li breakup on a 28Si target near the Coulomb barrier through an angular distribution measurement, a's were recorded in coincidence with deuterons in order to determine exclusively the breakup of lithium. Preliminary results are analysed and are discussed, in a discretized coupled channel framework (CDCC).